A natural agonist of mosquito TRPA1 from the medicinal plant Cinnamosma fragrans that is toxic, antifeedant, and repellent to the yellow fever mosquito Aedes aegypti - Inocente, Edna Alfaro; Shaya, Marguerite; Acosta, Nuris; Rakotondraibe, L. Harinantenaina; Piermarini, Peter M. (PLOS Neglected Tropical Diseases, 2018)
Plants produce various secondary metabolites that offer a potential source of novel insecticides and repellents for the control of mosquito vectors. Plants of the genus Cinnamosma are endemic to, and widely-distributed throughout, the island of Madagascar. The barks of these species are commonly used in traditional medicines for treating a wide range of maladies. The therapeutic nature of the bark is thought to be associated with its enrichment of pungent drimane sesquiterpenes, which elicit antifeedant and toxic effects in some insects. Here we test the hypothesis that a bark extract of Cinnamosma fragrans (CINEX) and its major drimane sesquiterpenes are insecticidal, antifeedant, and repellent to Aedes aegypti, the principal mosquito vector of chikungunya, dengue, yellow fever, and Zika viruses. We demonstrate that CINEX is 1) toxic to larval and adult female mosquitoes, and 2) antifeedant and repellent to adult female mosquitoes. Moreover, we show that cinnamodial (CDIAL), a sesquiterpene dialdehyde isolated from CINEX, duplicates these bioactivities and exhibits similar toxic potency against pyrethroid-susceptible and -resistant strains of Ae. aegypti. Importantly, we show that CDIAL is an agonist of heterologously-expressed mosquito Transient Receptor Potential A1 (TRPA1) channels, and the antifeedant activity of CDIAL is dampened in a TRPA1-deficient strain of Ae. aegypti (TRPA1-/-). Intriguingly, TRPA1-/- mosquitoes do not exhibit toxic resistance to CDIAL. The data indicate that modulation of TRPA1 is required for the sensory detection and avoidance of CDIAL by mosquitoes, but not for inducing the molecule’s toxicity. Our study suggests that CDIAL may serve as a novel chemical platform for the development of natural product-based insecticides and repellents for controlling mosquito vectors.